(untitled) (Medico Legal Update, 2021)
The current study was conducted in Al-Diwania Teaching Hospital/Oncology Division and Middle Furat Center for Cancerous Tumors in Al-Najaf, Babil Health Department/Marjan Hospital, Babil Health Department/Imam Al-Sadiq Hospital and Medical City Department/Al-Amal Hospital for the treatment of tumors and continued for the period from 2/10/2019 6/5/2020 60 samples were taken from patients diagnosed with colorectal cancer and 30 samples from non-infected people as a control group, with ages ranging from 33 years to 80 years for both groups . The results showed an increase in the level of Creatinine in the patient group compared to the control group and it was the highest in the radiotherapy group, followed by the chemotherapy group and then the control group. The results showed high significant differences between the three groups (p <0.001), and there were significant differences between the radiotherapy group. And a chemotherapy group. Through the results, it was found that the average level of Creatinine increased in the radiotherapy and chemotherapy groups compared to the control group. The results showed that the mean of AST was highest in the radiotherapy group, followed by the chemotherapy group and then the control group. The results showed high significant differences between the three groups (p <0.001). Through the results, it was found that there were no significant differences between the radiotherapy group and the chemotherapy group in the average level of the AST enzyme. It was also found that the average level of AST enzyme was higher for the radiotherapy and chemotherapy groups compared to the control group. The results of the current study showed the highest mean ALT enzyme in the radiotherapy group, followed by the chemotherapy group compared to the control group. The results showed high significant differences between the three groups (p<0.001) and significant differences between the radiotherapy group and the chemotherapy group. ALT for the radiotherapy and chemotherapy groups compared to the control group.